2016
DOI: 10.1016/j.jssc.2015.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Crystal growth of incommensurate members of 2H-hexagonal perovskite related oxides: Ba4M Pt3−O9 (M=Co, Ni, Cu, Zn, Mg, Pt)

Abstract: Millimeter sized crystals of six oxides of approximate composition Ba 4 M z Pt 3-z O 9 (M = Co, Ni, Cu, Zn, Mg, Pt) were grown from molten K 2 CO 3 fluxes and found to crystallize in a 2H hexagonal perovskite-related structure type. The compositions of these incommensurate structures, which belong to the A 3n+3m A' n B 3m+n O 9m+6n family of 2H hexagonal perovskite related oxides, were characterized by X-ray diffraction, energy dispersive spectroscopy, and magnetic susceptibility measurements. The specific syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Single crystals of La 9.15 Sr 1.85 Ir 4 O 24 , Nd 9 Sr 2 Ir 4 O 24 , and Pr 9.63 Sr 1.37 Ir 4 O 24 were grown out of a high-temperature strontium chloride flux, while polycrystalline powders of Ln 9 Sr 2 Ir 4 O 24 (Ln = La, Pr, Nd, Sm) were prepared via a standard solid-state route. Previous investigations of the platinum group metal (PGM) containing oxides in our group have focused primarily on using hydroxide fluxes at intermediate temperatures (500–800 °C) ,, and carbonate fluxes at high temperatures (900–1150 °C) to obtain single crystals of PGMs. In particular, lanthanide-containing iridates have often been crystallized using reactive alkali-metal hydroxides to synthesize various structure types, including double perovskites such as Ln 2 NaIrO 6 (Ln = La, Pr, Nd) .…”
Section: Resultsmentioning
confidence: 99%
“…Single crystals of La 9.15 Sr 1.85 Ir 4 O 24 , Nd 9 Sr 2 Ir 4 O 24 , and Pr 9.63 Sr 1.37 Ir 4 O 24 were grown out of a high-temperature strontium chloride flux, while polycrystalline powders of Ln 9 Sr 2 Ir 4 O 24 (Ln = La, Pr, Nd, Sm) were prepared via a standard solid-state route. Previous investigations of the platinum group metal (PGM) containing oxides in our group have focused primarily on using hydroxide fluxes at intermediate temperatures (500–800 °C) ,, and carbonate fluxes at high temperatures (900–1150 °C) to obtain single crystals of PGMs. In particular, lanthanide-containing iridates have often been crystallized using reactive alkali-metal hydroxides to synthesize various structure types, including double perovskites such as Ln 2 NaIrO 6 (Ln = La, Pr, Nd) .…”
Section: Resultsmentioning
confidence: 99%
“…2,3 Similarly, in the 2H-hexagonal perovskite related materials, one BO 6 trigonal bipyramid is substituted for two BO 6 octahedra. 4,5 A second method for family generation is through polyhedral insertion. This can be observed in the uranyl phosphates, where the extended phosphuranylite structure is generated from the phosphuranylite structure by insertion of uranyl square bipyramids into the uranyl chains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Shown in Figure 1, the two crystals can be distinguished by their columnar versus radiating habits and because crystals of (1) typically have blunt termination whereas crystals of (2) have a wedge-shaped termination. (4) were only obtained as minor side products, and attempts to target them were unsuccessful. Crystals of (3) were grown in a reaction of a mixture of 1/4 mmol UF 4 , 1.5 mmol TiO 2 , and 1 mmol SiO 2 covered by a mixture of 11 mmol CsCl and 9 mmol CsF in a covered 1.2-cm-diameter by 5.7-cm-height cylindrical silver crucible heated according to the previously described heating scheme.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Investigation of the magnetic properties of complex platinum group metal containing perovskites has been conducted for decades, both by our ,,,,,,, and other groups. ,,,,,,,,,,,,,,, Among these, iridates are of particular interest for their electrical and magnetic properties and, as a heavy 5 d element, iridium experiences strong spin orbit coupling that competes with crystal field effects, causing observed physical properties to be highly sensitive to changes in the local chemical environment . In a structure as easily tunable as a perovskite, there is significant interest in studying how changes in chemical environment manifest themselves in observed magnetic and electrical properties of iridates. , A study conducted by Jordan et al that investigated these effects in a family of hexagonal perovskites BaIr x Fe 1– x O 3‑δ ( x = 0.2, 0.3, 0.6) concluded that even a small difference in Ir content (BaIr 0.2 Fe 0.8 O 3−δ versus BaIr 0.3 Fe 0.7 O 3−δ ) resulted in significant variation of both structure and observed magnetic properties.…”
Section: Introductionmentioning
confidence: 99%